ROMICAT II: More Data Evaluating CT-First for Acute Chest Pain ED Triage - Buckley, Rita (MD Conference Express, 2012)
The use of coronary computed tomography for screening patients that present in emergency departments (EDs) with acute chest pain shortens length of stay compared with standard ED evaluation, according to the Rule Out Myocardial Infarction Using Computer-Assisted Tomography II Trial [ROMICAT II; NCT01084239].